Perbandingan Metode AHP dan TOPSIS untuk Pemilihan Karyawan Berprestasi - Musri Iskandar Nasution; Abdul Fadlil; Sunardi Sunardi (STMIK Budi Darma, 2022)
This study designed a system to determine outstanding employee selection using a Decision Support System (DSS) with the Analytical Hierarchy Process (AHP) method and the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). The purpose of this study is to analyze the accuracy in making decisions. The stages of this research are collecting employee data and criteria data, then weighting the criteria and assessment, after that the calculation uses the AHP and TOPSIS methods, and the last step is the analysis of the calculation results and the calculation of accuracy. The criteria used are attendance, years of service, permission, and discipline. Implementation for building applications using the PHP programming language and MySQL database. The results of the calculation of the accuracy obtained by the AHP method are 100%, as well as the TOPSIS method at 100%. The results of the AHP calculation show that the first rank results are obtained with a value of 0.02525, namely employees with code K8, while the results of the TOPSIS calculation show that the first rank results are obtained with a value of 0.955236913, namely employees with code K8. This shows that the two methods have the same results in determining the first rank of employees, however the TOPSIS method is better than AHP because the TOPSIS calculation process is carried out twice normalization so that it does not produce the same value.